Formation of tertiary amides and H2 by dehydrogenative coupling of primary alcohols with secondary amines catalyzed by ruthenium bipyridine-based pincer complexes - Srimani, Dipankar; Balaraman, Ekambaram; Hu, Peng; Ben-David, Yehoshoa; Milstein, David (Advanced Synthesis & Catalysis, 2013)
Dehydrogenative coupling of primary alcohols with secondary amines to form tertiary amides and dihydrogen (H2) is efficiently catalyzed by bipyridyl-based ruthenium pincer complexes (0.2–1 mol%) under neutral conditions (in case of the dearomatized complexes), or with added catalytic amount of base. The reaction is sensitive to steric hindrance; in the case of amidation of bulky secondary amines a less sterically hindered complex is more efficient. Selective acylation of primary amines in the presence of secondary amines was also demonstrated.